Georgian Agro-Sphere Development Priorities and Ways of Carrying Out Some Improvements (Economic and Political Thought, 2020)
The paper presents the main problems in the agricultural sector in Georgia and the conceptual model for eliminating these problems, which is based on certain qualitative assumptions and combines the ideas containedin the broad concept. Today, Georgia’s agricultural sector faces many problems and challenges. Reducing the number of places needed for agriculture in the world not only makes agricultural products more expensive, but also poses a threat of a global food crisis. The natural-climatic conditions enable Georgia to produce ecologically clean products. The demand for such products is growing. Nowadays, the proper use of Georgia’s natural-climatic conditions and the revival of agriculture is a precondition for the development of the country’s economy. Using the rich natural resources effectively will contribute to the developmentof the country’s economy and improve the living conditions of the population in the future.Given the current reality, the development of national agricultural production is vital for the security of the country. However, it is necessary to emphasize the fact that the policy of eliminating only one shortcoming in the agro-sector will not bring results to the country. However, it is impossible to solve the problems of the agro-sector separately, apart from the development of the country’s economy. Assistance to the agro-industry will only work if the right policies are implemented to develop long-term and stable economic processes.
Keywords: agro-sphere, agro-bank, agro centre, specialized foundations